History of The Development of The Principle of Delegatus Non-Potes Delegare and Its Implementation - Al-Fatih, Sholahuddin; Fadli, Moh. (Arena Hukum, 2024)
The origin of the principle of delegatus non potes delegare is often debated in academic circles. This principle is essential because it is the basis for the origins of several policies and other legal rules, such as delegated legislation. This article traces the origins of the delegatus non potes delegare principle and the development of delegated legislation in several countries, including Indonesia. Using legal research methods with conceptual and historical approaches, this article finds that the delegatus non potes delegare principle was first used in Paris, France, in 1566. Thereafter, the use of the principle continued to develop until its implementation in delegated legislation. This article provides an overview of implementing delegated legislation in several countries, namely, the United States, United Kingdom, Germany, Netherlands, France, India, Nigeria, Australia, Indonesia and in one supra-national region, namely, the European Union. Three critical aspects must be considered in the implementation of delegated legislation: the arrangement, the supervisory body/institution, and the form of supervision.